Development of TPACK-Based Physics Magazine as Teaching Material for High Schools: A Study on Rotational Dynamics and Rigid Body Equilibrium - Junaida; Fitriyawany; Ilyas, Zahriah (Pendidikan Fisika FITK UIN Sunan Kalijaga, 2023)
This study aims to develop a physics teaching magazine based on Technological Pedagogical and Content Knowledge (TPACK) for senior high school students, focusing on rotational dynamics and equilibrium of rigid bodies. Employing a Research and Development (R&D) approach with the 4-D model, the process encompassed definition, design, and development stages. The magazine's content and media aspects were validated by experts, achieving feasibility scores of 94% and 87.9%, respectively. The magazine was evaluated by students of SMAN 1 Lembah Seulawah Aceh Besar, with results indicating strong acceptance and effectiveness as a learning medium. While the study confirms the potential of TPACK-based interactive learning materials in science education, its limited scope and sample size suggest caution in generalizing the findings. Future research should expand the scope, involve larger samples, and integrate diverse technological tools. This research contributes to the discourse on digital competencies in science education, emphasizing the need for innovative materials and continuous professional development.